Large-scale production of cellulose-binding domains : adsorption studies using CBD-FITC conjugates - Pinto, João Ricardo (2006)
A method for the gram-scale production of cellulose-binding domains (CBD) through the proteolytic digestion of a commercial nzymatic preparation (Celluclast) was developed. The CBD obtained, isolated from Trichoderma reesei cellobiohydrolase I, is highly pure and heavily glycosylated. The purified peptide has a molecular weight of 8.43 kDa, comprising the binding module, a part of the linker, and about 30% glycosidic moiety. Its properties may thus be different from recombinant ones expressed in bacteria. CBDfluorescein isothiocyanate conjugates were used to study the CBD-cellulose interaction. The presence of fluorescent peptides adsorbed on crystalline and amorphous cellulose fibers suggests that amorphous regions have a higher concentration of binding sites. The adsorption is reversible, but desorption is a very slow process.